The Construction of Fandom Storytelling in Goncharov, A Scorsese Fanfilm - Freire-Sánchez, Alfonso; García Avis, Isadora; Vidal-Mestre, Montserrat (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This paper explores the digital discourse and fandom storytelling about Goncharov, a fanfilm attributed to Scorsese. By combining digital ethnography and discourse analysis, the characteristics of this original and collaborative transmedia narrative are defined, along with the roadmap that it has followed to turn from meme into fanfilm and urban legend. The results of this research are confronted with theories on fandom storytelling, and enable the comparison of Goncharov with historical phenomena. Ultimately, this study demonstrates the ability of fans to expand a story and to create new mixed narratives of diluted authorship, which then translate into new cultural products.